2016
DOI: 10.1111/apaa.12079
|View full text |Cite
|
Sign up to set email alerts
|

9 Social Inequality and Access to Services in Premodern Cities

Abstract: We use spatial analytical methods to illuminate one aspect of the urban experience: equity of access to facilities that provide material, religious, and assembly services. We compare three cities known from archaeology (Teotihuacan, Tikal, and Empuries) and three historical cities (Bhaktapur, Chester, and Lamu). Some neighborhoods had better access to service facilities than others, pointing to ancient patterns of spatial inequality. Data on house size suggest that status also impacted service access. Greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…Monte Albán, also collectively organized, was interlinked through a web of roads (Blanton 1978), as were other Classic period Valley of Oaxaca centers, such as El Palmillo (Feinman and Nicholas 2004). Site plans and the deployment of accessways provide starting points for the assessment of the distribution of public good in Mesoamerican cities, but more quantitative analyses also are underway (e.g., Dennehy et al 2016;Smith et al 2016b;Stanley et al 2016). Such efforts, although offering a constructive path forward, involve a complex web of assumptions and have to date not employed a means of measuring/assessing access to certain services and goods on a per capita basis.…”
Section: Public Goodsmentioning
confidence: 99%
“…Monte Albán, also collectively organized, was interlinked through a web of roads (Blanton 1978), as were other Classic period Valley of Oaxaca centers, such as El Palmillo (Feinman and Nicholas 2004). Site plans and the deployment of accessways provide starting points for the assessment of the distribution of public good in Mesoamerican cities, but more quantitative analyses also are underway (e.g., Dennehy et al 2016;Smith et al 2016b;Stanley et al 2016). Such efforts, although offering a constructive path forward, involve a complex web of assumptions and have to date not employed a means of measuring/assessing access to certain services and goods on a per capita basis.…”
Section: Public Goodsmentioning
confidence: 99%
“…15 To examine these issues, the arguments must be extended beyond ideological spheres and to matters economic. To account for both the self-aggrandizing nature of Maya lords compared to most pre-Hispanic Mesoamerican rulers, and how they were unable or unwilling to offer subaltern householders much in the way of public goods (e.g., wide thoroughfares, broad open plazas), 16 we might look toward the ways in which lordly power was funded. 17 Prior generations of scholars, hinged by the appropriation of Marx and Wittfogel to pre-Hispanic Mesoamerica, 18 presumed that Maya lords fostered their positions through primordial legacies of local land ownership or direct control of the economy; but neither idea yet has ample empirical grounding.…”
Section: Economic Underpinningsmentioning
confidence: 99%
“…Study of ancient purchase contracts within the Near East has shown that the cost of housing varied depending on its placement inside the city (Veenhof 1996, 257–60). Archaeologists have attempted to address this issue by comparing neighbourhood and household access to services, such as markets or religious buildings (Dennehy et al 2016), and these could be usefully combined with our inequality work. A more significant issue is that the use of household buildings as a proxy may remove particular classes of society from the equation altogether.…”
Section: Measuring Inequality In the Present And The Pastmentioning
confidence: 99%